A Pictorial Review on Acute Pancreatitis: Definitions and Diagnosis - Xiao, Bo (Emerging Trends in Disease and Health Research Vol. 8, 2022)
The present study aims to evaluate the early pancreatic fluid collections following acute pancreatitis on MRI. Acute pancreatitis is a frequent inflammatory condition that affects the pancreas, peripancreatic tissues, and distant organs. Acute pancreatitis is classified as mild, moderately severe, or severe according to the new Atlanta classification of 2012. Acute fluid collection terminology has undergone significant revisions in the classification. The study also aimed to provide an image-rich overview of different morphologic characteristics of early-stage (within 4 wks. after symptom onset) local complications associated with acute pancreatitis by computed tomography or magnetic resonance imaging; to clarify confusing imaging concepts for pancreatic fluid collections and underline standardised reporting nomenclature; to aid communication among treating physicians; and to facilitate the implications for gastrointestinal surgery. Radiologists should be fully aware of the standardised imaging nomenclature on the basis of associated morphologic descriptions. It is necessary for accurate documentation and reporting of academic research, and it is also important to direct implications of care plans for patients with acute pancreatitis.